2009
DOI: 10.1007/s11244-009-9343-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ammonia Formation During the Purge of a Lean NO x Trap

Abstract: The aim of this work was to study the formation of ammonia during the regeneration step of a commercial lean NO x Trap catalyst in real conditions. Experiments were carried out on an engine test bench equipped with 2.2 L common rail diesel engine. The aftertreatment system was composed of a commercial NSR monolith catalyst with a volume of 2.2 L. This material was composed of platinum, palladium and rhodium, as active components, with barium oxide and alumina as storage component and support, respectively. Cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The 6 understanding of NSR technology has been hampered by the fact that various (usually non-7 realistic) reaction conditions were often used and a very large number of model materials with 8 varying formulations were investigated [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]. 9 Several studies have been devoted to commercial NSR materials [23,24,25,26] and in 10 situ FTIR studies [27,28,29,30], but rarely the combination of the two has been reported. One 11 of the difficulties associated with commercial samples is the large number of components 12 present, making difficult the interpretation of in situ/operando IR spectra.…”
Section: Introductionmentioning
confidence: 99%
“…The 6 understanding of NSR technology has been hampered by the fact that various (usually non-7 realistic) reaction conditions were often used and a very large number of model materials with 8 varying formulations were investigated [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]. 9 Several studies have been devoted to commercial NSR materials [23,24,25,26] and in 10 situ FTIR studies [27,28,29,30], but rarely the combination of the two has been reported. One 11 of the difficulties associated with commercial samples is the large number of components 12 present, making difficult the interpretation of in situ/operando IR spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nitrates on the storage material will be reduced to NH 3 in O 2 -poor conditions. 48 2.3. Selective Catalytic Reduction (SCR).…”
Section: Study Of De-no X Methodsmentioning
confidence: 99%
“…In the case of ammonia as a reductant, previous studies have shown that it behaves similar to H 2 , with the same NO x conversion efficiency [55,56]. On the other hand, some literature data have revealed a difference in NH 3 versus H 2 reactivity towards stored NO x , for different catalyst compositions [50].…”
Section: Nh 3 Versus H 2 Reduction Of Nitrites/nitratesmentioning
confidence: 96%